The role of the currency sale window in the stability of the dinar exchange rate and its reflection on inflation (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The: currency Auction is one of the monetary policy tools created after 2003, in order to keep pace with the changes that the monetary and financial policies will witness from financial openness and expectations of high levels of liquidity after international economic restrictions. It is necessary to re-evaluate the work of the currency Auction from time to time and observation its efficiency in adjustment the exchange rate And its reflection on the general level of prices as one of the objectives of its inception, and during the analytical aspect, it was confirmed that the currency Auction for selling the currency had a major role in adjustment the exchange rate and controlling inflation levels, due to the market’s dependence on the external import of commodities, whether consumer or capital, as the stability of the exchange rate led to The stability of the general level of prices, but the adjustment of the parallel exchange rate through the currency Auction was at the expense of foreign reserves, as it is observe in a number of years of study that the sales of the currency Auction exceeded its purchases, in order to meet the need for demand for the dollar and this was done through the withdrawal from Foreign reserves to meet the need, whether in cash or through transfers to cover the value of imports, and this makes the levels of foreign reserves hostage to world oil prices due to rent for the Iraqi economy.